Early childhood and special education - Nwokah, Eva E.; Sutterby, John A., 1966- (Bingley, U.K. : Emerald, 2014)
Some chapters focus on interventions for the child, and others on training for the parents and professionals. The combination of current information and evidence contained in these chapters includes an emphasis on the importance of supporting families with different linguistic and cultural backgrounds, and indicates how team support (including families as part of the team) is crucial for these children. Parents of children with special needs may have their own challenges and this may create an additional need for support and resources for the family and the professional. The dynamic interaction between provider or teacher, theoretical approaches and curriculum used, and the childs' individual needs is what maximizes the impact of any intervention. The information is useful for early care and preschool teachers, early intervention providers, therapists, psychologists and administrators.
Reflective supervision and its impact on early childhood intervention / Christopher Watson ... [et al.] -- Engaging first generation immigrant parents of young children with exceptionalities / Hsuying C. Ward -- Supporting vocabulary development in Latino preschoolers : cultural and linguistic considerations / Lucía I. Méndez -- Interaction interventions for young children with disabilities / Ling-Ling Tsao, Juhee Sung -- Improvising with challenging behavior : creating new performances with children in early childhood special education / Barbara E. O'Neill -- The impact of a summer camp for adolescent mothers and their young children / Eva Nwokah, Susan Cupito, Deana McQuitty.
Print version record
Keywords: Education -- Special Education -- General; Education -- General; Primary & middle schools; Teaching of gifted students; Education; Early childhood special education